NOVELTIES IN BRAZILIAN BEGONIACEAE I: two new species from Bahia - Kollmann, Ludovic Jean Charles (Phytotaxa, 2019)
Two new species of Begonia from Bahia state, Brazil are described as Begonia micheliniana and Begonia charlesjarosiana. Begonia micheliniana is morphologically similar to Begonia polygonifolia and Begonia fagifolia. Begonia charlesjarosiana is morphologically similar to Begonia angularis. The new species grow in hygrophilous Atlantic Forest of Bahia state. Description, comparisons with morphologically similar species, etymology, taxonomic comments, illustrations, map and conservation statuses of the new species are also provided.